Maternal Western diet age‐specifically alters female offspring voluntary physical activity and dopamine‐ and leptin‐related gene expression. Issue 12 (9th August 2017) - Ruegsegger, Gregory N.; Grigsby, Kolter B.; Kelty, Taylor J.; Zidon, Terese M.; Childs, Thomas E.; Vieira‐Potter, Victoria J.; Klinkebiel, David L.; Matheny, Michael; Scarpace, Phillip J.; Booth, Frank W.
ABSTRACT: Prenatal overnutrition affects development into adulthood and influences risk of obesity. We assessed the transgenerational effect of maternal Western diet (WD) consumption on offspring physical activity. Voluntary wheel running was increased in juvenile (4–7 wk ofage), but decreased in adult (16–19 wk of age), F1 female WD offspring. In contrast, no wheel‐running differences in F1 male offspring were observed. Increased wheel running in juvenile female WD offspring was associated with up‐regulated dopamine receptor (DRD)‐1 and ‐2 in the nucleus accumbens (NAc) and with down‐regulated Lepr in the ventral tegmental area (VTA). Conversely, decreased wheel running by adult female WD offspring was associated with down‐regulated DRD1 in the NAc and with up‐regulated Lepr in the VTA. Body fat, leptin, and insulin were increased in male, but not in female, F1 WD offspring. Recombinant virus (rAAV) leptin antagonism in the VTA decreased wheel running in standard diet but not in WD F1 female offspring. Analysis of F2 offspring found no differences in wheel running or adiposity in male or female offspring, suggesting that changes in the F1 generation were related to in utero somatic reprogramming. Our findings indicate prenatal WD exposure leads to age‐specific changes in voluntary physical activity in female offspring that are differentially influenced by VTA leptin antagonism.—Ruegsegger, G. N., Grigsby, K. B., Kelty, T. J., Zidon, T. M., Childs, T. E., Vieira‐Potter, V. J., Klinkebiel, D. L., Matheny, M., Scarpace, P. J., Booth, F. W. Maternal Western diet age‐specifically alters female offspring voluntary physical activity and dopamine‐ and leptin‐related gene expression. FASEB J. 31, 5371–5383 (2017). www.fasebj.org